Plastic waste and microplastic issues in Southeast Asia - Ng, Chi Huey; Mistoh, Mohd Aizzan; Teo, Siow Hwa; Galassi, Andrea; Ibrahim, Azreen; Sipaut, Coswald Stephen; Foo, Jurry; Seay, Jeffrey; Taufiq‐Yap, Yun Hin; Janaun, Jidon (Frontiers in Environmental Science, 2023)
Plastic pollution on lands and oceans is a pressing environmental issue to date. The pilling up of waste accumulation has caused severe irreversible impacts and consequences to marine life, ecosystems, and the environments rooted in the lack of good waste collection, treatment, and management systems. The limited resources and infrastructures constantly challenge waste management in Southeast Asia. Hence, we examine the current plastic situation and issues in the Southeast Asian region, followed by understanding the issues of existing waste management systems in those countries. Next, we will examine the current practices applied in tackling plastic pollution. In addition, forging collective commitment and actions among the governments, private sectors, social organizations, stakeholders, and consumers as the key players in ending plastic pollution will be reviewed.